Tourism, remittances, and foreign investment as determinants of economic growth: Empirical evidence from selected Asian economies - Mosab I. Tabash; Suhaib Anagreh; Bilal Haider Subhani; Mamdouh Abdulaziz Saleh Al-Faryan; Krzysztof Drachal (Economies, 2023)
This research discovers how international tourism affects the economic growth of selected Asian states, e.g., Bangladesh, China, India, Pakistan, and Sri Lanka, throughout 2001-2019. To attain this objective, we have employed various regression estimation approaches, e.g., Fixed Effect Model (FEM) and Fully Modified Ordinary Least Square (FMOLS) technique. The statistical results of the applied techniques reveal that international tourism activities have a positive and significant effect on the GDP growth rate because such kinds of activities considerably contribute to creating opportunities that lead to hoist economic activities and economic growth. Moreover, an influx of tourism increases tourism activities and operations, which opens further doors to opportunities and generates revenue for the government. Similarly, the GDP per capita has been positively and significantly influenced by international tourism activities. The government and host country should emphasize the activities and operations regarding tourism and should also concentrate on the dynamic role, importance, and sensitivity of tourism operations in under-analyzed economies. This research brings a new arrangement of the variable, which has never been considered in prior literature.
Keywords: Q43; Z30; Q55; 330; FDI; international tourism; labor force; personal remittances